Thünensche Ringe der Biogaserzeugung: Der Einfluss der Transportwürdigkeit nachwachsender Rohstoffe auf die Rohstoffwahl von Biogasanlagen; Thuenen Rings of Biogas Production - the Effect of Differences in Transport Costs of Energy Crops in the Choice of Renewable Resources by Biogas Plants - Matthias Schulze Steinmann; Karin Holm-Mul̈ler (German Journal of Agricultural Economics (GJAE), 2010)
– This paper discusses how differences in transport costs of energy crops affect the choice of feedstock used in biogas production. This is done by optimizing feedstock demand subject to transportation distances of the different crops. For this a von Thuenen type model is applied to the feedstock demand of biogas plants. In addition to yields in terms of quantity and energy concerning the different crops and the costs of having them available, the profitability of the fermentation plant must be considered. It is shown that silage maize is the most profitable crop for medium distances, but gives way to winter wheat as distances increase. Our analysis suggests that even bigger plants than today can be sustained exclusively with silage maize. Key words: Thuenen Rings; transportation logistics; energy crops; biogas production
Keywords: 330